Penerapan Pendekatan Science, Environment, Technology, and Society (SETS) untuk Meningkatkan Kemampuan Literasi Sains Peserta Didik - Andini Pertiwi; Sitti Rahma Yunus; Muh. Tawil (Celebes Science Education, 2025)
This study aims to determine: 1) how much the improvement of science literacy abillity of students in class VIII UPT SPF SMP Negeri 54 Makassar after applying the SETS approach, 2) whether there is a difference in the average score of significant improvement in the science literacy abillity of students in class VIII UPT SPF SMP Negeri 54 Makassar before and after applying the SETS approach. This research is a pre-experimental design with a One Group Pretest-Posttets Design research design. The population of this study were all students of class VIII UPT SPF SMP Negeri 54 Makassar as many as 3 classes with a total of 91 students. Sampling through purposive sampling technique so as to obtain VIII C with a total of 24 students. The research instrument was a science literacy test. Data were analyzed with descriptive and inferential statistics. The results of the analysis concluded that 1) the increase in the science literacy abillity of students in class VIII UPT SPF SMP Negeri 54 Makassar who were taught using the Science, Environment, Technology and Society (SETS) approach of 0,31 was in the medium category, 2) there was a significant difference in the average score of the increase in the science literacy abillity of students in class VIII UPT SPF SMP Negeri 54 Makassar before and after the application of the SETS approach.